2021
DOI: 10.1007/s00520-021-06512-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a supportive care strategy in men with prostate cancer receiving androgen deprivation therapy at a regional cancer centre: a survey of patients and clinicians

Abstract: Purpose To understand how frequently exercise is discussed and/or prescribed as a supportive care measure and the barriers and facilitators to exercise uptake for men with prostate cancer receiving androgen deprivation therapy (ADT) at a regional cancer centre. Methods An observational, cross-sectional study was conducted at a regional cancer centre in three stages: (1) Retrospective chart review of men with prostate cancer undergoing ADT to identify the frequency of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
1
Order By: Relevance
“…Information on maintaining a healthy lifestyle was identified as lacking for rural cancer survivors in seven studies 22,39–44 . Specifically, there was a clear need for more information on diet and exercise, with six studies reporting unmet needs for information on these topics 22,39–43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information on maintaining a healthy lifestyle was identified as lacking for rural cancer survivors in seven studies 22,39–44 . Specifically, there was a clear need for more information on diet and exercise, with six studies reporting unmet needs for information on these topics 22,39–43 .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies suggested that written care plans or information sheets were needed for rural cancer survivors 28,29,39,44,50,56,66 . These were thought to be particularly useful for referring back to at a later time 56,66 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear gap between research into the benefits of exercise throughout the cancer care continuum and the incorporation of exercise into the standard of care. Elbourne, Soo (151) reported that fewer than 30% of clinicians working with prostate cancer survivors were aware of referral pathways for a supervised exercise program, and less than 16% of clinicians engaged in conversations with survivors about exercise (151). Though the integration of exercise as adjuvant medicine into the cancer treatment plan was low, nearly 73% of the clinicians in the study agreed that exercise counseling should be incorporated into cancer care (151).…”
Section: Multidisciplinary Approachesmentioning
confidence: 95%
“…Elbourne, Soo (151) reported that fewer than 30% of clinicians working with prostate cancer survivors were aware of referral pathways for a supervised exercise program, and less than 16% of clinicians engaged in conversations with survivors about exercise (151). Though the integration of exercise as adjuvant medicine into the cancer treatment plan was low, nearly 73% of the clinicians in the study agreed that exercise counseling should be incorporated into cancer care (151). In a similar survey by the American Society of Clinical Oncology, 78.9% of oncology clinicians supported recommending physical activity to cancer survivors, yet less than 23% referred survivors to exercise programming (152).…”
Section: Multidisciplinary Approachesmentioning
confidence: 99%